THE UNIQUE NATURE OF GISSAR STATE RESERVE - Kiryigitov Khurshid Botirovich; Nabieva Nilufar Vinamin kizi (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, the nature of the Gissar State Reserve of the Republic of Uzbekistan, which attracts tourists, about the diversity of plants and animals, their unique waterfalls, There are many unexplored caves in the Gissar State Reserve and it is possible to identify new and unique species of plants and animals that can be found in these caves.